2016
DOI: 10.1002/2016gl070170
|View full text |Cite
|
Sign up to set email alerts
|

The impact of glacier geometry on meltwater plume structure and submarine melt in Greenland fjords

Abstract: Meltwater from the Greenland Ice Sheet often drains subglacially into fjords, driving upwelling plumes at glacier termini. Ocean models and observations of submarine termini suggest that plumes enhance melt and undercutting, leading to calving and potential glacier destabilization. Here we systematically evaluate how simulated plume structure and submarine melt during summer months depends on realistic ranges of subglacial discharge, glacier depth, and ocean stratification from 12 Greenland fjords. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
193
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(201 citation statements)
references
References 64 publications
(69 reference statements)
6
193
2
Order By: Relevance
“…The glacier releases subglacial discharge via two large channels, but their corresponding melting contributes only 15 % of the total melt of the glacier front. Furthermore, Carroll et al (2016) showed that the simulated melt rate of a single cone plume is about 2 orders of magnitudes lower than the spatially averaged melt rate by Fried et al (2015). Thus we investigate whether the LP model can calculate the average melting by assuming that the 250 m deep glacier is undercut below 50 meters depth, with an angle of 77 • to achieve the observed undercutting (Fig.…”
Section: West Greenland Glaciersmentioning
confidence: 99%
“…The glacier releases subglacial discharge via two large channels, but their corresponding melting contributes only 15 % of the total melt of the glacier front. Furthermore, Carroll et al (2016) showed that the simulated melt rate of a single cone plume is about 2 orders of magnitudes lower than the spatially averaged melt rate by Fried et al (2015). Thus we investigate whether the LP model can calculate the average melting by assuming that the 250 m deep glacier is undercut below 50 meters depth, with an angle of 77 • to achieve the observed undercutting (Fig.…”
Section: West Greenland Glaciersmentioning
confidence: 99%
“…Subglacial discharge exits the glacier at the grounding line, rises buoyantly along the ice front due to its lower density relative to the ambient fjord water, and flows down-fjord once neutral buoyancy is reached (Motyka et al, 2003;Jenkins, 2011;Cowton et al, 2015). In fjords with shallow glacier grounding line depths (<500 m) like KNS, summer discharge meltwater plumes often reach neutral buoyancy and horizontally enter the fjord within the upper 100 m of the water column (Carroll et al, 2016). The outflow forced by the subglacial discharge establishes an estuarine circulation cell, drawing in coastal waters from the shelf, which flow in a layer beneath the fresher outflow (Motyka et al, 2003;Mortensen et al, 2011).…”
Section: Study Areamentioning
confidence: 99%
“…Although producing weak plumes, subglacial discharge of this magnitude can generate point source SMRs of between 2 and 4 m d −1 . Due to their lower velocity, weak plumes, such as those expected via basal frictional melting, reach neutral buoyancy before reaching the fjord surface (Christoffersen et al, 2012;Slater et al, 2015;Carroll et al, 2016). However, close to the glacier grounding line, where ice tongue keel depth is greatest, weaker plumes will likely still reach and melt the base of the ice tongue.…”
Section: Temporal Variability In Smrmentioning
confidence: 99%
“…). Yet ice sheet catchment delineation remains a relatively uncertain undertaking, e.g., due to uncertainties in bedrock topographical maps (Carroll et al, 2016) that were minimized by Lindbäck et al (2015) by constructing a detailed bedrock map from ice-penetrating radar measurements. To our advantage, the Kangerlussuaq catchment is relatively wide at 30+ km near the ice sheet margin (Fig.…”
Section: Surface Mass Balance Modelingmentioning
confidence: 99%